2013
DOI: 10.1016/j.psychres.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Internalized stigma and quality of life among persons with severe mental illness: The mediating roles of self-esteem and hope

Abstract: Research has revealed the negative consequences of internalized stigma among people with serious mental illness (SMI), including reductions in self-esteem and hope. The purpose of the present study was to investigate the relation between internalized stigma and subjective quality of life (QoL) by examining the mediating role of self-esteem and hope. Measures of internalized stigma, self-esteem, QoL, and hope were administrated to 179 people who had a SMI. Linear regression analysis and Structural Equation Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
107
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 43 publications
(73 reference statements)
16
107
4
6
Order By: Relevance
“…Our results agree with previous findings that selfstigma reduces the self-esteem of an individual with mental illness (Corrigan & Watson, 2002;Corrigan et al, 2006;Lysaker et al, 2012). Also, our findings were aligned with studies that found negative impacts of self-stigma on an individual's SQoL (Chan & Mak, 2014;Mashiach-Eizenberg et al, 2013;Lin et al, 2016). In addition, our results agree with the mediation model proposed by MashiachEizenberg et al (2013) that self-esteem is a mediating factor between an individual's self-stigma and his or her SQoL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with previous findings that selfstigma reduces the self-esteem of an individual with mental illness (Corrigan & Watson, 2002;Corrigan et al, 2006;Lysaker et al, 2012). Also, our findings were aligned with studies that found negative impacts of self-stigma on an individual's SQoL (Chan & Mak, 2014;Mashiach-Eizenberg et al, 2013;Lin et al, 2016). In addition, our results agree with the mediation model proposed by MashiachEizenberg et al (2013) that self-esteem is a mediating factor between an individual's self-stigma and his or her SQoL.…”
Section: Discussionsupporting
confidence: 92%
“…For example, one study found that relationships between self-stigma and SQoL were different between groups that engaged and groups that did not engage in community service programs (Huang & Lin, 2015). However, we cannot tackle the treatment issue due to the nature of the cross-sectional design in the previous study (Mashiach-Eizenberg et al, 2013). Specifically, the treatment is dynamic, and its effects cannot be measured in a short period of time.…”
mentioning
confidence: 99%
“…Por un lado, la teoría del intercambio social (Connell et al, 2012), la cual indica que toda interacción puede generar respuestas positivas o negativas, pudiendo provocar síntomas de estrés, ansiedad y ser perjudiciales, por lo que se va generando una respuesta de evitación, reduciendo su calidad de vida (Hansson, 2006). Por otro, el efecto del estigma social y el autoestigma o internalización del estigma (Connell et al, 2012;Corrigan et al, 2009;Mashiach-Eizenberg et al, 2013), consistente en que las personas con TMS son conscientes del estigma público hacia la enfermedad mental y adoptan esas actitudes estigmatizantes. Como consecuencia, los usuarios llegan a asimilar lo que Corrigan et al, (2009) denominaron el modelo de "¿por qué intentarlo?"…”
Section: Consideraciones Finalesunclassified
“…Hope has been identified as an integral factor in recovery for people with schizophrenia (Deegan, 1996;Noordsy et al, 2002;Resnick et al, 2005) and has been described as the most basic step to recovery, in that one must believe recovery is possible and begin to look to the future with optimism (Jacobson and Greenley, 2001). Greater hope has also been associated with reduced symptoms, improved social functioning, a greater sense of personal recovery, greater activation in psychiatric treatment, and better quality of life in people diagnosed with schizophrenia (Kukla et al, 2013a;Kukla et al, 2013b;Lysaker et al, 2004;Lysaker et al, 2008;Mashiach-Eizenberg et al, 2013;Oles et al, 2015).…”
Section: Introductionmentioning
confidence: 99%